A postmodern analysis: tracing the elements of politics, war and trauma in graphic narratives in Marjane Satrapi’s Persepolis and Joe Sacco’s Palestine - Gomes, Susan Andrea (Brac University, 2019)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2019.